Rac1 at the crossroad of actin dynamics and neuroinflammation in Amyotrophic Lateral Sclerosis - D’Ambrosi, Nadia; Rossi, Simona; Gerbino, Valeria; Cozzolino, Mauro (Frontiers in Cellular Neuroscience, 2014)
Rac1 is a major player of the Rho family of small GTPases that controls multiple cell signaling pathways, such as the organization of cytoskeleton (including adhesion and motility), cell proliferation, apoptosis and activation of immune cells. In the nervous system, in particular, Rac1 GTPase plays a key regulatory function of both actin and microtubule cytoskeletal dynamics and thus it is central to axonal growth and stability, as well as dendrite and spine structural plasticity. Rac1 is also a crucial regulator of NADPH-dependent membrane oxidase (NOX), a prominent source of ROS, thus having a central role in the inflammatory response and neurotoxicity mediated by microglia cells in the nervous system. As such, alterations in Rac1 activity might well be involved in the processes that give rise to Amyotrophic Lateral Sclerosis (ALS), a complex syndrome where cytoskeletal disturbances in motor neurons and redox alterations in the inflammatory compartment play pivotal and synergic roles in the final disease outcomes. Here we will discuss the genetic and mechanistic evidence indicating the relevance of Rac1 dysregulation in the pathogenesis of ALS.